The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1016/j.jfms.2010.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological findings and disease staging of feline infectious peritonitis: 51 cases from 2003 to 2009 in Taiwan

Abstract: Fifty-one cats histopathologically confirmed to have been naturally infected by feline infectious peritonitis (FIP), were collected to analyse the clinical and laboratory findings and to characterise disease staging. Effusive FIP was found in 33 cats, non-effusive FIP in 12 cats, and mixed-type in six cats. Highly significant decreases in haematocrit and albumin levels and an increase in total bilirubin level were noted in both effusive and non-effusive FIP, at first presentation and before death. In serial bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 11 publications
9
75
0
13
Order By: Relevance
“…Critical evaluation is necessary for a cat to be diagnosed with FIP. Diagnosis is based on evaluation of history, symptoms, hematological and biochemical parameters, diagnostic tests, radiology and tissue biopsy results (Shelly et al, 1988;Sparkes et al, 1994;Hartmann et al, 2003;Addie et al, 2009;Pedersen, 2009;Sharif et al, 2010;Tsai et al, 2011). It has been reported that up to 12% of FCoV infected cats develop FIP (Hartmann, 2005;Addie et al, 2009;Pedersen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Critical evaluation is necessary for a cat to be diagnosed with FIP. Diagnosis is based on evaluation of history, symptoms, hematological and biochemical parameters, diagnostic tests, radiology and tissue biopsy results (Shelly et al, 1988;Sparkes et al, 1994;Hartmann et al, 2003;Addie et al, 2009;Pedersen, 2009;Sharif et al, 2010;Tsai et al, 2011). It has been reported that up to 12% of FCoV infected cats develop FIP (Hartmann, 2005;Addie et al, 2009;Pedersen, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Em alguns casos, a suspeita clínica de peritonite infecciosa felina pode estar relacionada à semelhança de sinais clíni-cos entre as duas enfermidades e faixa etária em que elas se apresentam (Pedersen 2009, Tsai et al 2010. Em parte dos casos a suspeita clínica foi de intoxicação, relacionada ao fato de ambas as doenças apresentarem convulsão como sinal clínico e curso agudo (Arnot et al 2011).…”
Section: Discussionunclassified
“…1 In one study in Taiwan, 88% of 51 FIP-confirmed cats were less than 2 years old. 72 The risk decreases to 4% when cats reach 36 months of age. 65 The disease is overrepresented in certain pure breeds, but the incidence of FIP can vary greatly between regions and countries.…”
Section: Fip Incidence and Risk Factorsmentioning
confidence: 99%
“…65 The disease is overrepresented in certain pure breeds, but the incidence of FIP can vary greatly between regions and countries. Abyssinian, Australian mist, Bengal, Birman, British shorthair, Burmese, Cornish rex, Himalayan, Persian, ragdoll, and rex breeds have been suggested as risk factors, [71][72][73][74] but FIP development is probably more related to bloodlines within a breed than to breeds themselves. 59 It has been demonstrated that the development of FIP in certain lineages occurs at higher frequencies than other lineages, independently of environment, antibody titers, or viral shedding patterns.…”
Section: Fip Incidence and Risk Factorsmentioning
confidence: 99%